CBMS-05 COMPREHENSIVE METABOLOMIC ANALYSIS OF IDH1R132H CLINICAL GLIOMA SAMPLES REVEALS SUPPRESSION OF Β-OXIDATION DUE TO CARNITINE DEFICIENCY. (16th December 2019) - Miyata, Satsuki; Tominaga, Kaoru; Sakashita, Eiji; Urabe, Masashi; Onuki, Yoshiyuki; Gomi, Akira; Yamaguchi, Takashi; Mieno, Makiko; Mizukami, Hiroaki; Kume, Akihiro; Ozawa, Keiya; Watanabe, Eijyu; et al.
Abstract: BACKGROUND: Gliomas with isocitrate dehydrogenase 1 (IDH1) mutation have alterations in several enzyme activities, resulting in various metabolic changes. The aim of this study was to investigate the mechanism for the better prognosis of gliomas with IDH mutation by performing metabolomic analysis. METHODS: To comprehensively understand the metabolic state of human gliomas, we analyzed clinical samples obtained from surgical resection of glioma patients (grades II-IV) with or without the IDH1 mutation, and compared them with U87 glioblastoma cells overexpressing IDH1 or IDH1 R132H cDNA. We used capillary electrophoresis and liquid chromatography time-of-flight mass spectrometry for these analyses. RESULTS: In clinical samples of gliomas with IDH1 mutation, levels of 2-hydroxyglutarate (2HG) were significantly increased compared with gliomas without IDH mutation. Gliomas with IDH mutation also showed decreased 2-oxoglutarate and downstream intermediates in the tricarboxylic acid cycle and pathways involved in production of energy, amino acids, and nucleic acids. The marked difference in the metabolic profile in IDH mutant clinical glioma samples compared with that of mutant IDH expressing cells includes a decrease in β-oxidation due to acyl-carnitine and carnitine deficiencies. CONCLUSIONS: These metabolic changes may explain the lower cell division observed in IDH mutant gliomas and may be one mechanism of the better prognosis in IDH mutant gliomas.